Partisipasi Anggaran, Komitmen Organisasi dan Kinerja Manajerial dengan Gaya Kepemimpinan dan Budaya Organisasi sebagai Pemoderasi - Pemi Pangestu Andika (Magister Akuntansi Universitas Pancasila, 2019)
ABSTRACT The success of an organization in achieving its goals depends largely on managerial performance. This study aims to analyze organizational participation and commitment to managerial performance through leadership styles and organizational culture as moderating variables. This study uses a quantitative approach by testing the hypothesis to see the correlation between budgetary participation and organizational commitment to managerial performance with leadership style and organizational culture as a moderating variable. The leadership style does not moderate budget participation and organizational commitment to managerial performance. Organizational culture moderates budget participation in managerial performance but organizational culture does not moderate the organizational commitment to managerial performance in the scope of the Directorate of Disease Prevention and Control of the Ministry of Health. ABSTRAK Keberhasilan suatu organisasi dalam mencapai tujuan sebagian besar tergantung pada kinerja manajerial. Penelitian ini bertujuan untuk menganalisis partisipasi penyusunan dan komitmen organisasi terhadap kinerja manajerial melalui gaya kepemimpinan dan budaya organisasi sebagai variable moderasi. Gaya kepemimpinan tidak memoderasi partisipasi anggaran dan komitmen organisasi terhadap kinerja manajerial. Budaya organisasi memoderasi partisipasi anggaran terhadap kinerja manajerial tetapi budaya organisasi tidak memoderasi antara komitmen organisasi terhadap kinerja manajerial di ruang lingkup Direktorat Pencegahan Dan Pengendalian Penyakit Kementerian Kesehatan. JEL Classification: M41, H83